In vitro alpha glucosidase inhibition, in vivo antidiabetic activity and hypolipidemic effect of tepal extracts of Musa paradisiaca in stz-induced diabetic mice - Muhammad Abdurrazak
The use of medicinal plants as source of remedies for the treatment of many diseases dated back to prehistory and people of all continents have this old tradition. In the present study, tepals of Musa paradisiaca was evaluated for phytochemical screenin, the total content of flavonoid and phenolics, in vitro a-glucosidase inhibition and in vivo antidiabetic efficacy in streptozotocin (STZ)- induced diabetic mice. Diabetic mice were administered 500 mg/kg per day of methanolic tepal extract (MTE) orally for one month and compared with untreated mice for the following studies. The mice were sacrificed and blood collected for key biochemical markers such as, blood glucose, creatinine, urea, uric acid, total protein, lipid profile, aminotransferases and alkaline phosphatase. The histopathological studies of pancreas, liver and kidney were also performed. Preliminary phytochemical screening reveals the presence of phenolics, flavonoids, glycosides, terpenoids, tannins and alkaloids. MTE has the richest content of both phenolics (4.27 mg GAE/g) and flavonoids (0.25mg QE/g) in comparison with aqueous and ethanolic tepal extracts. The result of the inhibitory effect of these extracts on a-glucosidase activities also revealed that MTE was the most potent inhibitor of a-glucosidase (with IC50 60±0.14 µg/mL) followed by ethanolic tepal extract (ETE) and then aqueous tepal extract (ATE) in a dose dependent manner, though the various extracts were not significantly different (p>0.05) at 1 mg/mL. Elevated blood glucose, creatinine, urea and uric acid levels were significantly (p<0.05) reverted back to near normal in STZ-induced diabetic mice with oral administration of MTE. Plasma protein, lipid profile, transaminases and alkaline phosphatase were also significantly reverted back to near normalcy (p<0.05) after the treatment. Histopathological analysis indicated tissue damages in the diabetic untreated mice; treatment with MTE exhibits the tissue protective role (of pancreas and liver) against peroxidation damage, thus signifying tissue integrity maintenance of MTE. In conclusion, it can be inferred that the in vitro and in vivo antidiabetic therapeutic efficacy of tepals of Musa paradisiaca may be attributed to the presence of phytochemicals such as phenolics, flavonoids, alkaloids etc.